Accurate Radar-Based Heartbeat Measurement Using Higher Harmonic Components - Itsuki Iwata; Kimitaka Sumi; Yuji Tanaka; Takuya Sakamoto (IEEE Access)
This study proposes a radar-based heartbeat measurement method that uses the absolute value of the second derivative of the complex radar signal, rather than its phase, in combination with the variational mode extraction method, which is a type of mode decomposition algorithm. We show that the proposed second-derivative-based approach can amplify the heartbeat component in the radar signals effectively. We also confirm that the use of the variational mode extraction method provides an efficient way to emphasize the heartbeat component when amplified via the second-derivative-based approach. We then demonstrate estimation of the interbeat intervals of the heart by using the proposed approach in combination with the topology method, which is an accurate interbeat interval estimation method. The performance of the proposed method is quantitatively evaluated using data acquired from eleven participants that were measured using a millimeter-wave radar system. Compared with the conventional methods based on the phase of the complex radar signal, our proposed method can achieve higher precision when estimating the heart’s interbeat intervals; the correlation coefficient for the proposed method was increased by 0.20 and the root mean square error was reduced by 23%.